Lost in Translation? Challenges and Opportunities for Raising Health and Safety Awareness among a Multinational Workforce in the United Arab Emirates - Tom Loney; Robert Fletcher Cooling; Tar-Ching Aw (Safety and Health at Work, 2012)
The United Arab Emirates (UAE) has experienced tremendous economic and industrial growth in the petroleum, airline, maritime and construction sectors, especially since the discovery of oil reserves. Mass recruitment of low skilled or unskilled laborers from less-developed countries has been utilized to satisfy the manpower demands of these fast paced industrial developments. Such workforce recruitment has created an unusual populace demographic, with the total UAE population estimated at 8.3 million, composed of 950,000 Emiratis, with the remainder being multinational expatriate workers, with varying educational qualifications, work experience, religious beliefs, cultural practices, and native languages. These unique characteristics pose a challenge for health and safety professionals tasked with ensuring the UAE workforce adheres to specific occupational health and safety procedures. The paper discusses two case studies that employ a novel multimedia approach to raising health and safety awareness among a multinational workforce.